Lexical Features of Interlingual Homonyms in Modern Persian, Dari and Tajik - Akhmedova, Mastura N.; Yuzmukhametov, Ramil T.; Abrorov, Iles M.; Beloglazova, Inessa G.; Bayzoev, Azim (Journal of History Culture and Art Research, 2019)
The relevance of the researched problem is caused by the need to study the lexical features of the modern Persian, Dari and Tajik languages, and to show students of a real linguistic situation when studying the Persian language. The aim of the article is to consider the lexical features of interlingual homonyms in modern Persian, Dari and Tajik. The leading approach in the studying of this issue is a problem-thematic approach. The study of interlingual homonyms in terms of their features and the review of the situations in which they are used in the Persian and Tajik languages shows the possible approaches to the description of their semantics. This is a new direction in the modern Persian lexicography, which is of a great scientific benefit. The submissions of this article may be useful in the teaching of the modern Persian, Tajik, Dari languages as well as when lecturing on the lexicology and dialectology of Persian, Tajik, Dari.